AA.VV. - Atlas of The Functional City. Ciam 4 and Comparative Urban Analysis - Monclús Fraga, Javier (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2016)
Evelien van Es, Gregor Harbusch, Bruno Maurer, Muriel Pérez, Kees Somer, Daniel Weiss (eds.)Atlas of The Functional City. Ciam 4 and Comparative Urban AnalysisZúrich, Publisher Thoth et gta Verlag, 2014, 480 pág. Publicado en cooperación con la Fundación Van Eesteren-Fluck & Van Lohuizen  y con el  gta Archiv, ETH, Zúrich. Formato: 24 x 30 cm.Idioma: inglés. 89,50 €